2021
DOI: 10.1186/s40510-021-00390-4
|View full text |Cite
|
Sign up to set email alerts
|

Global survey to assess preferences when attending virtual orthodontic learning sessions: optimising uptake from virtual lectures

Abstract: Objectives Understanding the issues concerning the conducting of virtual orthodontic learning sessions (VOLSs) is essential. This study aims to identify attendees- and host-related aspects that could optimise learning and uptake from the VOLSs. Methodology Fourteen pre-validated questions were anonymously and electronically sent to 3000 orthodontic residents and specialists globally. The survey included demographic questions and questions to gauge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Survey results showed a significant increase in study time, with flexibility and interactivity being the top benefits and distractions (poor internet connection, family distractions and the timing of the tutorials) as the main challenges [4]. Similarly, results from a global survey assessing participant preferences for virtual online orthodontic learning sessions concluded that accessibility of post videos was instrumental in optimizing learning by improving memory retention [5]. However, engaging learners' interests was mainly associated with the acquisition of new learning styles, knowledge, and social networking [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey results showed a significant increase in study time, with flexibility and interactivity being the top benefits and distractions (poor internet connection, family distractions and the timing of the tutorials) as the main challenges [4]. Similarly, results from a global survey assessing participant preferences for virtual online orthodontic learning sessions concluded that accessibility of post videos was instrumental in optimizing learning by improving memory retention [5]. However, engaging learners' interests was mainly associated with the acquisition of new learning styles, knowledge, and social networking [5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, results from a global survey assessing participant preferences for virtual online orthodontic learning sessions concluded that accessibility of post videos was instrumental in optimizing learning by improving memory retention [5]. However, engaging learners' interests was mainly associated with the acquisition of new learning styles, knowledge, and social networking [5].…”
Section: Introductionmentioning
confidence: 99%